ON SOME COLOURLESS FLAGELLATES FROM JAVA AND BRASIL - SKVORTZOV, B. V. (REINWARDTIA, 1974)
Two new monotypie genera (Kizakimonas bogoriensis and Hoehne mastix saopaulensis) and six other new species (four in Tetramitus and two in Balliamonas) of colourless flagellates are described based on samples collected in Bogor and Sao Paulo.